LEARNING AND TEACHING BETWEEN ENJOYMENT AND BOREDOM AS REALIZED BY THE STUDENTS: A SURVEY FROM THE EDUCATIONAL FIELD - Al-Shara, Ibrahim (European Scientific Journal, ESJ, 2015)
This study aimed at investigating the factors that affect students' enjoyment in learning and teaching as recognized them self's. To achieve the purpose of this study the researcher developed a study instrument consisted of 45 items and distributed to five sub-domains. The study followed a descriptive analytical method. Validity and reliability were tested, then distributed on (637) students from upper elementary grades. Results of the study showed that "the implementation of learning resources" (83.74%) is the most important factor that affects students' enjoyment. The lowest factor that influences students' enjoyment of learning is "the teachers' teaching style" (56.93%). Further, the results showed that some factors such as: the implementation of learning resources, student's role in the classroom, and the administrative role are more influential in favor of female students. In addition, students' of high achievement increases their enjoyment level during utilizing learning resources. However, the impact of teacher's role on students' enjoyment was the least affected factor for students who have lower achievement level. Furthermore, there are no statistically significant differences related to the level of the school. In light of the findings, the researcher recommends that there is a need for providing opportunities that increase the active role of students. Further, administrators should engage more with students' activities. Crucial factors that increase enjoyment levels of students include focusing on implementing learning resources in teaching and encouraging students who have low achievement levels in the activities.